Proclaiming the Divine Logos to the Man of the Future - Torrijos-Castrillejo, David (Studia Nauk Teologicznych PAN, 2021)
This paper studies the cooperation of theology in the new evangelization in societies of ancient Christian tradition which are suffering an advanced process of secularization. It begins with Spain, where a recent debate on the influence of Christian intellectuals on social life suggests the ineffectiveness of ecclesiastical resources in transmitting the rich Catholic doctrinal heritage. Then the author deals with the idiosyncrasy of contemporary man, which lies near the one of the immediate future’s man: an uprooted subject who does not believe that life has any meaning, is deeply marked by emotivism and attaches little significance to truth. The theology of tomorrow cannot feed this emotivism but must be proactive in its own way. The proclamation of the Gospel is not different from the exposition of the Church’s doctrine. To detach evangelization from the teaching of Christian doctrine cannot help the encounter with Christ. In order to succeed in transmitting this doctrine by making it suggestive, theologians should work together with experts in communication.